The Ethics of AI: Power, Critique, Responsibility - Mühlhoff, Rainer (Bristol University Press, 2025)
Available open access digitally under CC-BY-NC-ND licence. In a world where artificial intelligence increasingly influences the fabric of our daily lives, this accessible book offers a critical examination of AI and its deep entanglement with power structures. Rather than focusing on doomsday scenarios, it emphasises how AI impacts our everyday interactions and social norms in ways that fundamentally reshape society. By examining the different forms of exploitation and manipulation in the relationship between humans and AI, the book advocates for collective responsibility, better regulation and systemic change. This is a resounding manifesto for rethinking AI ethics through a power-aware lens. With detailed analysis of real-world examples and technological insights, it is essential reading for anyone invested in the future of AI policy, scholarly critique and societal integration.